Pengaruh Konsep Kepemimpinan Islam terhadap Perkembangan Lembaga Pendidikan Islam di Indonesia - Bahri, Syaiful; Murni Yanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the influence of the concept of Islamic leadership on the development of education under the auspices of the Ministry of Religious Affairs (Kemenag). The research method used is descriptive qualitative with a literature study and content analysis approach, using data sources in the form of books, articles, and official Islamic education websites. The results indicate that the concept of Islamic leadership, based on the Quran and Hadith, emulating the qualities of the Prophet Muhammad (peace be upon him), such as honesty, trustworthiness, intelligence, and communication, has a positive impact on the progress of Islamic educational institutions. However, several challenges and shortcomings in its implementation remain, such as abuse of power, the challenges of modernization, and issues of differences in schools of thought and gender. The conclusion of this study is that the successful implementation of the concept of Islamic leadership in education depends heavily on the quality and integrity of the leader, as well as his or her ability to innovate without deviating from Islamic values. Keywords: Islamic Leadership, Islamic Education, Kemenag, Educational Management